Kaposi’s sarcoma regression after long term treatment of m-TOR inhibitors and cancellation of immunosuppressive therapy in patient after kidney transplantation - A. D. Sapozhnikov; A. D. Perlina; I. N. Dymkov (Вестник трансплантологии и искусственных органов, 2019)
A case of observation of a patient who developed Kaposi’s sarcoma after kidney transplantation is presented. For the purpose of its treatment, conversion from tacrolimus to everolimus, courses of administration of prospidin were applied, in General, the intensity of immunosuppressive therapy was reduced. Stable remission was achieved only after removal of the renal transplant and complete withdrawal of immunosuppressive therapy.